The Impact of SAK EMKM Socialization, Accounting Comprehension, and Information Technology on MSME Financial Statement Quality through Implementation - Sariningsih, Eka; Via Amelia; Aza Azlina Md Kassim; Ovie Amanda; Faizal Muztama (RUBINSTEIN, 2026)
This study aims to examine the effect of SAK EMKM socialization, accounting comprehension, and information technology on the quality of financial statements of micro-scale MSMEs, with SAK EMKM implementation as an intervening. Conducted in Kemiling District, Bandar Lampung, it uses a quantitative approach with data from 40 MSMEs analyzed PLS-SEM (SmartPLS). The results show that only accounting comprehension significantly affects SAK EMKM implementation, while socialization and technology do not. SAK EMKM implementation also does not significantly influence financial statement quality and fails to mediate the relationships. This study is subject to certain constraints, particularly the relatively small number of observations and the restricted geographic coverage of the research area. This study highlights the importance of accounting comprehension for improving MSME financial practices. The finding reveal the models explain a substantial proportion of variance in financial statement quality, highlighting the centrality of targeted socialization programs and literacy in improving MSME reporting practices, as well as the facilitating role of appropriate implementation of SAK EMKM. Policy implications include prioritizing comprehensive socialization campaigns, strengthening accounting training for MSME owners, and aligning technology solutions with SAK EMKM procedures.